TISSUE REACTIONS INDUCED BY DENTAL PULP CAPPING MATERIALS - Alexandru Sitaru; Tudor Hantoiu; Monica Monea (European Scientific Journal, ESJ, 2014)
Objective: The aim of this article is to evaluate the biocompatibility of materials used in pulp capping procedures, by measuring the degree of inflammation induced by these products after subcutaneous implantation in rats. Materials and methods: we used 12 animals divided in 3 study groups and 1 control group; implants with Mineral trioxide Aggregate (MTA), Life cement (Kerr) and Calxyd (Spofa Dental) were placed in subcutaneous tissue and histological evaluation was carried out after 7, 14 and 21 days. Results: We obtained comparable results between MTA and Life cement, which demonstrates that these materials have similar degrees of biocompatibility. Conclusion: Based on this experimental study, MTA and calcium hydroxide containing cements express similar biocompatibilities, but this is not enough in order to eliminate the letter from every day dental practice. Further clinical studies are necessary in order to evaluate the potential of MTA to induce dentin bridge formation on exposed dental pulp.